الافات االجتماعية وعلاقتها بالتحصيل الدراسي لدى تلاميذ التعليم املتوسط - السوفي,لخضر (University of Eloued جامعة الوادي, 2024)
هدفت الدراسة إلى استكشاف العلاقة بين الإدمان على التدخين واستخدام الإنترنت وتحصيل الطلاب في مرحلة التعليم المتوسط ، من وجهة نظر مستشار التوجيه وكانت الدراسة الميدانية في المتوسطات دائرة جامعة ولاية المغير وبالاعتماد على منهج وصفي والمسح الشامل قدرت عينة الدراسة ب 34 طالباً وطالبة ، أظهرت النتائج وجود علاقة ارتباطية ذات دلالة إحصائية 0.05 بين الإدمان على التدخين وكذا الإدمان على الإنترنت والتحصيل الدراسي للطلاب، حيث كشفت الدراسة أن الطلاب المدمنين على التدخين أو الإنترنت يعانون من أداء دراسي أقل مقارنة بأقرانهم غير المدمنين، مما يشير إلى تأثير سلبي يؤثر على تركيزهم وقدرتهم على الانخراط في العمل الدراسي . The Relationship Between Smoking and Internet Addiction and Academic Achievement Among Middle School Students: A Guidance Counselor's Perspective Abstract: This study aimed to explore the relationship between smoking addiction, internet addiction, and academic achievement among middle school students, from the perspective of a guidance counselor. The field study was conducted in middle schools within the jurisdiction of Al-Magheer University, using a descriptive approach and comprehensive survey. The study sample consisted of 34 male and female students. The results revealed a statistically significant correlation (p < 0.05) between smoking addiction, internet addiction, and academic achievement of students. The study found that students addicted to smoking or the internet tend to exhibit lower academic performance compared to their non-addicted peers, indicating a negative impact on their focus and ability to engage in academic work
من وجهة نظر مستشاري التوجيه والارشاد المدرسي والمهني
Keywords: الآفات الاجتماعية; الإدمان على التدخين; الإدمان على الانترنت; Social issues; smoking addiction; internet addiction